1996
DOI: 10.1144/jm.15.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Precise chitinozoan dating of Ordovician impact events in Baltoscandia

Abstract: -The chitinozoan biostratigraphy of four Ordovician impact craters has been investigated. Three of these (Tviiren, Kardla and Lockne) contain complete sequences of early Caradoc agc, while the Granby crater contains rocks of late Arenig age yielding two bentonitic horizons at their top. Chitinozoans, together with graptolites and other planktic organisms, were the first to invade the craters after the impact event. It has therefore been possible to date the impact events with a precision of less than one milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 15 publications
4
93
0
1
Order By: Relevance
“…3) in the Tandsbyn Gully (Lindstrom et a/., 1996) ( i e . , West of Ynntjarn 1, Ynntjbsbacken 1 and Lappgrubban 1, now believed to be situated in an erosional channel through the outer crater (Tandsbyn Gully)) have previously been discussed by Grahn and NBlvak (1993) and Grahn et al (1996). In this study, four boreholes, the Lockne drillings DBH 1 to 4 in the central part of the Lockne impact structure (Fig.…”
Section: Chitinozoan Biostratigraphysupporting
confidence: 51%
See 4 more Smart Citations
“…3) in the Tandsbyn Gully (Lindstrom et a/., 1996) ( i e . , West of Ynntjarn 1, Ynntjbsbacken 1 and Lappgrubban 1, now believed to be situated in an erosional channel through the outer crater (Tandsbyn Gully)) have previously been discussed by Grahn and NBlvak (1993) and Grahn et al (1996). In this study, four boreholes, the Lockne drillings DBH 1 to 4 in the central part of the Lockne impact structure (Fig.…”
Section: Chitinozoan Biostratigraphysupporting
confidence: 51%
“…12b) in samples of MAlingen I, and the absence of chitinozoan species from the underlying biozones, strengthen the arguments that the impact event occurred in the lower part of the L. dalbyensis zone. The finds of Laufeldochitina stenfor in boulders within the Lockne Breccia (basal resurge deposits) at Ynntjmsbacken 1 (Grahn et al, 1996) indicate that the youngest preimpact sediments hitherto found belong to the lower part of the Dalby Limestone. The sedimentary infill in the Lockne impact structure seems to have ceased at a time corresponding to the upper Belonechitina hirsuta Zone.…”
Section: Remarks On the Stratigraphymentioning
confidence: 97%
See 3 more Smart Citations